The Many Faces of Vitamin B 12 : Catalysis by Cobalamin-Dependent Enzymes - Banerjee, Ruma; Ragsdale, Stephen W. (Annual review of biochemistry, 2003)
▪ Abstract  Vitamin B 12 is a complex organometallic cofactor associated with three subfamilies of enzymes: the adenosylcobalamin-dependent isomerases, the methylcobalamin-dependent methyltransferases, and the dehalogenases. Different chemical aspects of the cofactor are exploited during catalysis by the isomerases and the methyltransferases. Thus, the cobalt-carbon bond ruptures homolytically in the isomerases, whereas it is cleaved heterolytically in the methyltransferases. The reaction mechanism of the dehalogenases, the most recently discovered class of B 12 enzymes, is poorly understood. Over the past decade our understanding of the reaction mechanisms of B 12 enzymes has been greatly enhanced by the availability of large amounts of enzyme that have afforded detailed structure-function studies, and these recent advances are the subject of this review.